1999
DOI: 10.1177/101053959901100103
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Health-Related Practices among University Students in Northeast Thailand

Abstract: The study aims at appraising gender differences in health-related practices, and health behaviour among university students of the Khon Kaen University, northeast Thailand, using a self-administered questionnaire. Of 539 university students, there were 155 males, 384 females, with mean ages 19.7 (+/- 1.2) and 19.6 (+/- 1.1) years, respectively. Persistent health problems were not significantly different between male and female students (12.9% vs. 15.4%). An average body mass index (BMI) was significantly diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 7 publications
5
24
0
Order By: Relevance
“…This is in line with previous findings (Al-Omari and Hamasha 2005;Covington 1996;Fukai et al 1999;Nanakorn et al 1999;Redford 1993;Sakki et al 1998). Women's more pronounced dental care behaviour may be related to the fact that women are more exposed to aesthetic advertisements and more inclined to be aware of the appearance of their lips, mouths and smiles (Dzierzak 1993).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This is in line with previous findings (Al-Omari and Hamasha 2005;Covington 1996;Fukai et al 1999;Nanakorn et al 1999;Redford 1993;Sakki et al 1998). Women's more pronounced dental care behaviour may be related to the fact that women are more exposed to aesthetic advertisements and more inclined to be aware of the appearance of their lips, mouths and smiles (Dzierzak 1993).…”
Section: Discussionsupporting
confidence: 82%
“…On the other hand women follow oral hygiene recommendations more thoroughly and draw upon more dental care (Al-Omari and Hamasha 2005;Fukai et al 1999;Nanakorn et al 1999;Sakki et al 1998). Most studies report the prevalence rates for oral health indicators for women and men separately without commenting on them.…”
Section: Background and Aimmentioning
confidence: 99%
“…Ostberg et al (17) found that females engage in better oral hygiene behavioral measures, possess a greater interest in oral health, and perceive their own oral health to be good to a higher degree than males. Nanakorn (18) and Kassak (19) found female university students to have better habits in terms of tooth brushing than male students, while Fukai et al found that females visited their dentists and brushed their teeth more often than males (20,21). Klemendz (22) reported that women used fluoride as a prophylactic tool approximately four times more often than men.…”
Section: Discussionmentioning
confidence: 99%
“…Factors identified to be associated with health behavior include sociodemographic factors [female gender (21)(22)(23)(24)(25)(26), socioeconomic status (27)(28)(29), educational achievement (30,31), social factors [social support (32), sense of coherence (25,33,34), religiosity or spirituality (32,35), sense of control (36,37)], and health variables [risk awareness (36,38), perceived health benefits (36,39,40), low depression (41), low levels of psychological distress (42,43)]. The purpose of this study was to assess the prevalence of health behaviors and its associated factors in a sample of Indian university students.…”
mentioning
confidence: 99%